The Impact of Severe Maternal Morbidity on Very Preterm Infant Outcomes - ZEITLIN, Jennifer (J Pediatr, 2019)
OBJECTIVE: To estimate the prevalence of severe maternal morbidity (SMM) among very preterm births and determine its association with very preterm infant mortality and morbidity. STUDY DESIGN: This study used New York City Vital Statistics birth and death records linked with maternal and newborn discharge abstract data for live births between 2010 and 2014. We included 6901 infants without congenital anomalies born between 24(+0) and 31(+6) weeks of gestation. SMM was identified as life-threatening conditions or life-saving procedures. Outcomes were first-year infant mortality, severe neonatal morbidity (bronchopulmonary dysplasia, severe necrotizing enterocolitis, Stage 3–5 retinopathy of prematurity and intraventricular hemorrhage Grades 3–4) and a combined outcome of death or morbidity. RESULTS: 12% of very preterm live-born infants had a mother with SMM. Maternal and pregnancy characteristics associated with occurrence of SMM were multiparity, being non-Hispanic black and preexisting health conditions, but gestational age and the percentage small for gestational age did not differ. Infants whose mothers experienced SMM had higher first-year mortality, 11.2% versus 7.7% without SMM, yielding a relative risk of 1.39 (95% confidence interval: 1.14–1.70) after adjustment for maternal characteristics, preexisting co-morbidities, pregnancy complications and hospital factors. Severe neonatal morbidity was not associated with SMM. CONCLUSIONS: Severe maternal morbidity is an independent risk factor for mortality in the first year of life among very preterm infants after consideration of other maternal and pregnancy risk factors.